Sociocultural Conditions of Society as A Determining Factor of Ecological Culture - Muratova Dildora (Scientific Trends, 2024)
In scientific terminology, the sociocultural environment refers to a space that reflects all conditions of human life activity. This environment encompasses all aspects of human life, from daily routines to spiritual and cultural life. The main elements of sociocultural include cultural-historical heritage, lifestyle practices, socio-psychological, spiritual-moral, political, and ecological culture. Cultural-historical heritage includes customs, traditions, values, and historical monuments passed down through generations. The artistic environment is associated with cultural treasures such as works of art, architectural monuments, literature, and music. While the socio-psychological environment encompasses societal relationships, customs, and moral norms, spiritual and moral values determine people's religious beliefs, ethical values, and spiritual worldview. The political environment includes the political system, laws, and governance principles in society, while the ecological environment reflects the relationship between nature and humans.
Keywords: Ecological culture; ecological safety; sociocultural transformation; social system; global climate change; natural environment.